A Case Study on Tamil Nadu Government’s Welfare Schemes to Motivate SMEs Manufacturing Wet Grinders in Coimbatore - Ganeshan, Hariharan (Prabandhan: Indian Journal of Management, 2013)
The present case study is a review of SMEs manufacturing wet grinders in Coimbatore region. This study describes and analyzes how the Tamil Nadu Government’s welfare scheme of providing table top wet grinders to women beneficiaries ( free of cost) impacts SMEs manufacturing wet grinders in the next five years. The study was conducted during the period from 2011-2012. The first phase distributed 2.5 million units of table top wet grinders to the Tamil women. Introducing such welfare schemes by the government is a huge opportunity for the SMEs in Coimbatore region in terms of grabbing business opportunities, increasing their business network, generating employment opportunities and bringing about socio-economic prosperity in the region. However, the small scale industry would not be able to undertake such a huge production of wet grinders in the absence of financial and governmental support. Hence, in addition to resolving the power shortage issue, availability of raw material and labour also needs to be increased, and the SME sector has to take every possible step to cash on this golden opportunity.